IMMUNOLOGICAL PARAMETERS IN BREAST CANCER PATIENTS UNDER BETALEUKIN ADJUVANT TREATMENT - M. Staheeva; E. Slonymskaya; N. Babyshkina; N. Cherdyntseva; A. Simbirtsev; A. Kladiev (Медицинская иммунология)
Abstract. We have examined the effect of betaleukin on the immune parameters in breast cancer (BC) patients treated with cytostatic drug and surgery. Intravenous application of betaleukin for 5 days just before adjuvant chemotherapy have been shown to prevent both the decrease of blood immune cell count and the damage of their functional activity in BC patients with lymph node involvement N0–1. BC patients with wide spreading lymph node metastases N2 showed the protection of blood neutrophil activity but not lymphocyte subset count following betaleukin administration and chemotherapy. Positive effect of betaleukin was found to depend upon the adaptive state of patients. Betaleukin in turn appeared to display the adaptogenic activity. (Med. Immunol., 2005, vol.7, № 1, pp 63572)